An Empirical Analysis of the Relationship Between Foreign Direct Investment, Stock Returns, and the Wider Economy in Brazil. - Tidbury, Marcus (2022)
This paper tests the impact of foreign direct investment on stock returns in Brazil over the period 2003–2019, using quarterly data on a range of metrics. Structural breaks are identified and controlled for within a single-equation and system- based cointegration framework, whilst (Vector) Error Correction and Vector Autoregression models employed to capture the long and short run dynamics between our variables, alongside Granger causality to measure the direction of the relationships. Our results follow the trend of the general literature, with variation displayed between our two cointegration models, despite both confirming the existence of a long-run relationship existing between our variables. In the long run, our system-based technique reports a significant positive effect of FDI, domestic investment, financial development, and the exchange rate on returns, with a speed of convergence to the long- run equilibrium of 31% per quarter. Our single-equation model reports a 65% speed of convergence, finding returns are positively impacted by financial development, trade openness and real GDP, whilst the effect of FDI appears insignificant. In the short run, our results lend support to the hypotheses that FDI crowds out domestic investment and that trade openness allows an economy to better absorb the benefits of FDI.